Comparison of oxidative stress levels among patients with primary open angle glaucoma(POAG) and primary angle closure glaucoma (PACG) closure glaucoma (PACG) - Chan, Fhun Lai (2016)
Introduction: Oxidative stress has been postulated to cause retinal ganglion cells death, trabecular meshwork degeneration leading resistance of aqueous outflow. Subsequently, it may lead to IOP elevation and glaucomatous optic neuropathy. Thus, it is worthwhile to look for the oxidative stress level in glaucoma patients. Detection of oxidative stress level in ocular tissue may perhaps provide insight into a role of oxidative stress in pathogenesis of glaucoma. Objective: Our objective was to compare the oxidative stress level in tears between glaucoma and agematched controls. The comparison of SOD, catalase and MDA level between POAG and PACG patients were also conducted. Methods: A cross sectional study was conducted between May 2014 and November 2015 involving patients with confirmed diagnosis of POAG and PACG attending eye clinic of two tertiary hospitals in Malaysia; Hospital Universiti Sains Malaysia and Hospital Raja Permaisuri Bainun. Age-match non glaucoma patients were recruited as controls. The detail medical history, ocular history and drug history such as antioxidant supplement were obtained through direct questioning from patients and medical record. Complete ophthalmic evaluations were conducted including Humphrey visual field analysis. Tear samples collected by using schirmer paper. Laboratory analysis was performed to test on SOD, catalase and MDA level of tears using commercially available immunological kits. Statistical analysis was done using Statistical Package for the Social Science (SPSS Inc Version 20). Independent ttest was used to compare the SOD, catalase and MDA level in tears between glaucoma and controls. Results: A total of 62 POAG patients, 57 PACG patients and 72 controls were recruited. Patients with glaucoma were older. Mean SOD and catalase level were slightly higher in glaucoma patients as compared to controls. Meanwhile mean MDA level was slightly lower in glaucoma patients compared with controls. However, there was no significant difference of SOD level (p=0.191), catalase level (p=0.259) and MDA level (p=0.309) between glaucoma and controls using multivariate analysis. There was no significant difference of SOD, catalase and MDA level between POAG and PACG patients. However, mean SOD activity was statistically significant higher in patients with POAG compared to controls after adjusting confounding factors (351.67 U/ml vs 315.12 U/ml), p=0.006) . Conclusions Quantification of oxidative stress level in tears is non invasive and easy. Catalase and MDA may not a play role in oxidative stress in glaucoma. SOD is a potential oxidative stress marker for POAG.